Forming induced wrinkling of composite laminates with mixed ply material properties; an experimental study. (November 2015) - Hallander, P.; Sjölander, J.; Åkermo, M.
Abstract: One disadvantage of multi-layer forming of unidirectional (UD) prepreg tape is the risk of out-of-plane wrinkling. This study aims to show how mixed ply material properties affect global wrinkling behaviour. An experimental study was performed using pre-stacked UD prepreg on a forming tool with varying cross sections. Parameters studied include local interply friction, effects of co-stacking and fibre stresses in critical fibre directions. Experimental evaluation was performed on out-of-plane defect height, type and location. The study shows that fibre stresses in some fibre directions were crucial for the shearing required to avoid wrinkling. The same fibre stresses may cause wrinkling if the lamina is stacked in a non-beneficial order. Changing the friction locally, or reducing the number of difficult combinations of fibre angles, improves the forming outcome slightly. However, in order to make a significant improvement, co-stacking or different fibre stacking is required.